Visceral Machines: Risk-Aversion in Reinforcement Learning with Intrinsic Physiological Rewards - McDuff, Daniel; Kapoor, Ashish (ICLR 2019, 2019)
As people learn to navigate the world, autonomic nervous system (e.g., “ﬁght or ﬂight”) responses provide intrinsic feedback about the potential consequence of action choices (e.g., becoming nervous when close to a cliff edge or driving fast around a bend.) Physiological changes are correlated with these biological preparations to protect one-self from danger. We present a novel approach to reinforcement learning that leverages a task-independent intrinsic reward function trained on peripheral pulse measurements that are correlated with humana autonomic nervous system responses. Our hypothesis is that such reward functions can circumvent the challenges associated with sparse and skewed rewards in reinforcement learning settings and can help improve sample efﬁciency. We test this in a simulated driving environment and show that it can increase the speed of learning and reduce the number of collisions during the learning stage.